PARP Inhibitors in Epithelial Ovarian Cancer - Taylor, Kristin N.; Eskander, Ramez N. (Recent Patents on Anti-Cancer Drug Discovery, 2018)
Background: Ovarian cancer remains the most common lethal gynecologic malignancy. The therapeutic gains with the use of traditional cytotoxic chemotherapy in advanced stage disease remain limited, reflecting the need for novel therapies. Poly(ADP-ribose) polymerase (PARP) inhibitors have recently demonstrated a significant therapeutic effect in patients with recurrent, high grade serous ovarian cancer, both in the treatment of existing disease and in prolonging the disease-free interval. Objective: The purpose of this article is to discuss PARP inhibitor use in patients with advanced stage ovarian cancer, and to extensively review the existing clinical literature and related patents. Methods: A comprehensive PUBMED literature review was conducted to identify all published phase 2 and phase 3 clinical trials involving PARP inhibitors in advanced epithelial ovarian cancer. Further, several patents related to PARP inhibitor use, companion diagnostic tests, and the development of biomarkers to predict PARP inhibitor responsiveness are described. Results: PARP inhibitors have demonstrated significant clinical activity in both BRCA deficient and wild-type patient cohorts, with all three FDA-approved PARP inhibitors demonstrating efficacy irrespective of BRCA mutation status in patients with advanced epithelial ovarian cancer. Conclusion: PARP inhibitors have emerged as an exciting new drug class in the treatment of epithelial ovarian cancer. Ongoing studies are aimed at improving our ability to identify ideal candidates for PARP inhibitor therapy, as well as to identify and target mechanisms of drug resistance, and novel combinatorial approaches.
Keywords: PARP inhibitor